An assessment of the utilisation of computers as teaching and learning resources: a case study of selected Gweru urban schools - Chitanana, Lockias (University of Zimbabwe, 2019)
Computers have a great potential to transform the teaching and learning process in our classrooms. However, the realisation of this potential depends on how much our teachers use this technology in their teaching. It is, therefore, important for us to know how teachers are making use of computers, so that we can determine where additional support is needed. As such, the primary aim of this study is to assess how teachers in Gweru urban schools are utilising computers in their classroom teaching. The data collected through a guestionnaire administered to 50 teachers indicate that computers have not been fully integrated into the teaching and learning process in the schools. Despite the fact that computers have been in schools for the past decade, there is evidence that the majority of the teachers is not well prepared to make use of computers as teaching and learning resources. Only a few teachers indicated that they are using computers in their teaching. Further investigation on how these teachers were using computers in their teaching revealed that the teachers were only using computers to reinforce the traditional teacher centred methods of teaching. It is clearly demonstrated by the findings of this research that the utilisation of computers as teaching and learning resources cannot be left to trial and error. In this regard, the research findings point to the need for both pre-service and in-service teacher training in computer skills as well as pedagogical skills which are prerequisites to the effective utilisation of computers as teaching and learning resources.